Severe Silver-Russell syndrome. - Donnai, D (1989)
Three children are described with severe Silver-Russell syndrome. Major medical problems occurred in the first two years of life in all three. Silver-Russell syndrome should be considered in the differential diagnosis of children with severe pre- and postnatal growth deficiency.